Evaluation Quality of Information, Education and Communication (IEC) Services at Pharmacy X in Semarang - Andiswara Pramesti; Wulan Kartika Sari Sari (VISIKES, 2026)
Satisfaction is a customer response to services that can meet needs and expectations. Patient satisfaction is a top priority that depends on the quality of pharmaceutical services provided. To increase patient satisfaction and patient understanding of the use of drugs, it is necessary to deliver Information, Education and Communication (IEC) which plays an important role in pharmaceutical services. This study aims to determine the characteristics of respondents who get (IEC) services and to determine the level of patient satisfaction with IEC services at Pharmacy “X” in Semarang. The sampling technique used was purposive sampling. This study uses a cross-sectional descriptive quantitative data analysis method. The results of data analysis of respondent characteristics show that most are female with ages 36–45 years, have a high school education, work as private employees, and are BPJS members. The measurement results on IEC services at Pharmacy “X” in Semarang show that of the five dimensions of service quality the percentage was very satisfied with an average of 84.48%. Pharmaceutical services in pharmacies are supported by pharmaceutical personnel who provide information, education, and communication on drug use, thereby increasing the accuracy of drug use and the success of patient therapy.